Design of Multivalent Inhibitors for Preventing Cellular Uptake - Schubertová, Veronika; Martinez-Veracoechea, Francisco J; Vácha, Robert (Scientific reports, 2017)
Cellular entry, the first crucial step of viral infection, can be inhibited by molecules adsorbed on the virus surface. However, apart from using stronger affinity, little is known about the properties of such inhibitors that could increase their effectiveness. Our simulations showed that multivalent inhibitors can be designed to be much more efficient than their monovalent counterparts. For example, for our particular simulation model, a single multivalent inhibitor spanning 5 to 6 binding sites is enough to prevent the uptake compared to the required 1/3 of all the receptor binding sites needed to be blocked by monovalent inhibitors. Interestingly, multivalent inhibitors are more efficient in inhibiting the uptake not only due to their increased affinity but mainly due to the co-localization of the inhibited receptor binding sites at the virion's surface. Furthermore, we show that Janus-like inhibitors do not induce virus aggregation. Our findings may be generalized to other uptake processes including bacteria and drug-delivery.
Keywords: Virus Internalization; Drug Design; Antiviral Agents; Molecular Dynamics Simulation; simulace molekulární dynamiky; internalizace viru; racionální návrh léčiv; antivirové látky